Both the assertion and the reason are incorrect.
To test the validity of the assertion, we can solve the equation:
3(t - 5) - 16t = 12 - 2(t - 3)
Expanding and simplifying, we get:
3t - 15 - 16t = 12 - 2t + 6
Combine like terms:
-13t - 15 = 18 - 2t
Add 13t to both sides:
-15 = 13 + 11t
Subtract 13 from both sides:
-28 = 11t
Divide by 11:
t = -28/11
Therefore, t does not equal -3.
Similarly, to test the reason, we can solve the equation:
8x + 3(x + 4) = 10x - 7
Expanding and simplifying, we get:
8x + 3x + 12 = 10x - 7
Combine like terms:
11x + 12 = 10x - 7
Subtract 10x from both sides:
x + 12 = -7
Subtract 12 from both sides:
x = -19
Therefore, x equals -19, not 19.
ASSERTION: If 3(t - 5) - 16t = 12 - 2(t - 3) , then t = - 3
REASON: If 8x + 3(x + 4) = 10x - 7 , then x = 19
1 answer